Optimalisasi Motorik Kasar Pada Anak Berkebutuhan Khusus Melalui Media Serbaneka : Swastika Farezhena, Ajeng Ayu Widiastuti - Farezhena, Swastika; Ayu Widiastuti , Ajeng (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2023)
Gross motor skills are the important skill for every child by involving the large muscles of all the limbs. These skills become the foundation for children to be master in other life skills. This is action research with a single subject. This study aims to train and optimize the strength of gross motor skills in a four-year-old boy with special needs at the 123 Kids therapy center. This study uses individual learning program by using various media, which various kinds of media that are obtained and found around the child. The results show that gross motor skills to maintain body balance through the activities such as (1) kicking the ball, (2) walking in a straight line, (3) walking on tiptoe, (4) putting the ball under the raised leg, (5) body balance, (6) airplane attitude, (7) Sunda manda, and (8) jumping on one leg can be improved with repetition and assistance.